Oral communication in higher education: an experience of standardized assessment - Ordinola Sandoval, Erika Vanessa (2023)
Oral communication is an essential competence in the academic and professional fields. However, evaluating it presents a challenge due to the difficulty in establishing observable and objective descriptions. The purpose of this study is to identify the level of development of oral communication skills achieved by students. To achieve this, a standardized evaluation system was implemented with a sample of 592 undergraduate students enrolled between the sixth and twelfth cycles at a private Peruvian university. The study concludes that students performed better in terms of content development, eye contact, and pronunciation, while difficulties were observed in fulfilling the communicative purpose, using gestures, and varying the tone of voice. The study concludes with recommendations for future experiences regarding standardized evaluation of oral communication.